Non-cancerous CT findings as predictors of survival outcome in advanced non-small cell lung cancer patients treated with first-generation EGFR-TKIs - Pakorn Prakaikietikul; Pattraporn Tajarenmuang; Phumiphat Losuriya; Natee Ina; Thanika Ketpueak; Thanat Kanthawang (PLoS ONE, 2025)
Purpose To identify non-cancerous factors from baseline CT chest affecting survival in advanced non-small cell lung cancer (NSCLC) treated with first-generation Epidermal Growth Factor Receptor-Tyrosine Kinase Inhibitors (EGFR-TKIs). Methods Retrospective study of 172 advanced NSCLC patients treated with first-generation EGFR-TKIs as a first-line systemic treatment (January 2012 to September 2022). Baseline CT chest assessed visceral/subcutaneous fat (L1 level), sarcopenia, and myosteatosis (multiple levels), main pulmonary artery (MPA) size, MPA to aorta ratio, emphysema, and bone mineral density. Cox regression analyzed prognostic factors at 18-month outcome. Results Median overall survival was 17.57 months (14.87–20.10) with 76 (44.19%) patients died at 18 months. Deceased had lower baseline BMI (21.10 ± 3.44) vs. survived (23.25 ± 4.45) (p < 0.001). Univariable analysis showed 5 significant prognostic factors: low total adiposity with/without cutoff [HR 2.65 (1.68–4.18), p < 0.001; 1.00 (0.99–1.00), p = 0.006;], low subcutaneous adipose tissue (SAT) with/without cutoff [HR 1.95 (1.23–3.11), p = 0.005; 0.99 (0.98–0.99), p = 0.005], low SAT index (SATI) with/without cutoff [1.74 (1.10–2.78), p = 0.019; 0.98 (0.97–0.99), p = 0.003], high VSR [1.67 (1.06–2.62), p = 0.026], and high MPA size with/without cutoff [2.23 (1.23–4.04), p = 0.005; 1.09 (1.04–1.16), p = 0.001]. MPA size, MPA size > 29 mm, and total adiposity ≤85 cm2 remained significant in multivariable analysis, adjusted by BMI [HR 1.14 (1.07–1.21), p < 0.001; 3.10 (1.81–5.28), p < 0.001; 3.91 (1.63–9.40), p = 0.002]. There was no significant difference of sarcopenic and myosteatotic parameters between the two groups. Conclusion In advanced EGFR-mutated NSCLC patients, assessing pre-treatment prognosis is warranted to predict the survival outcome and guide decision regarding EGFR-TKI therapy. Enlarged MPA size, low total adiposity, and low subcutaneous fat (lower SAT, lower SATI, and higher VSR) are indicators of poor survival. Large MPA size (>29 mm) or low total adiposity (≤85 cm2) alone predict 18-month death.